KERJASAMA BILATERAL CENTRUM TOT BEVORDERING VAN DE IMPORT UIT ONTWIKKELINGSLANDEN (CBI) DAN KEMENTRIAN PERINDUSTRIAN INDONESIA DALAM MENINGKATKAN KUALITAS PRODUK DAN KEMAMPUAN EKSPOR INDUSTRI KECIL MENENGAH (IKM) INDONESIA KE PASAR EROPA - Hanifa Muslimah, (2020)
The European market is one of Indonesia's main export destinations. This is because the European Union has an important role in increasing the participation of developing countries in the Global Production Chain (global production chain). This study aims to explain the problem of exports of Indonesian Small and Medium Industries (SMEs) in the European market and analyze the bilateral cooperation between the Dutch CBI and the Ministry of Industry in the food sector in 2013-2017 by providing technical assistance in the form of Export Training and Development of Business Support Organizations to SMIs in the food sector and the Ministry of Industry. As for the background of this collaboration, Indonesian SMEs have difficulty penetrating the European market due to the high standardization of the European market. The author uses the theory of bilateral cooperation and foreign assistance. This research was analyzed using qualitative methods. the result of this collaboration is to increase the achievement of the target export value of more than 7.9 million Euros.